Ansa cervicalis or ansa hypoglossi? A systematic review - Gustavo Henrique Pereira Boog; Flávio Carneiro Hojaij; Matheus Mychael Mazzaro Conchy; Renan da Silva Bentes; Flávia Emi Akamatsu; Alfredo Luiz Jácomo (Brazilian Journal of Otorhinolaryngology, 2025)
Objective: To conduct a literature review on the relationship between the ansa cervicalis (or ansa hypoglossi) and the hypoglossal nerve, discussing this disparity in terminology, and determine which of these terms is the most suitable to identify this important nerve structure. Methods: This is a systematic review of the literature based on studies found through a standardized search performed at the LILACS and MEDLINE/PUBMED databases; classic anatomy textbooks were also consulted. Results: Forty-five of the 3731 articles found in the scientific research databases were selected and six classic anatomy textbooks were included in the study. Controversies involving the ansa cervicalis were analyzed and the results clearly showed that most textbooks describe its relationship with the hypoglossal nerve as a temporal junction, with no exchange of nerve fibers. The ansa cervicalis contains fibers arising from the cervical cord, and not from the hypoglossal nerve. Conclusion: The term ansa cervicalis should be chosen to name this loop of nerves. The term ansa hypoglossi is not structurally correct, and should be abandoned in medical practice, the teaching of anatomy, and in scientific publications. Level of evidence: Level II.